Surgical Management of Complex Liver Trauma: A Single Liver Transplant Center Experience (2012)
Complex liver trauma often presents major diagnostic and management problems. Current operative management is mainly centered on packing, damage control, and early utilization of interventional radiology for angiography and embolization. In this retrospective observational study of patients admitted to the Mediterranean Institute for Transplantation and Advanced Specialized Therapies, Palermo, Italy, from 1999 to 2010, we included patients that underwent hepatic resection for complex liver injuries (grade I to Vaccording to the American Association for the Surgery of Trauma-Organ Injury Scale). Age, gender, mechanism of trauma, type of resection, surgical complications, length of hospital stay, and mortality were the variables analyzed. A total of 53 adult patients were admitted with liver injury and 29 underwent surgical treatment; the median age was 26.7 years. Mechanism was blunt in 52 patients. The overall morbidity was 30 per cent, morbidity related to liver resection was 15.3 per cent. Mortality was 2 per cent in the series of patients undergoing liver resection for complex hepatic injury, whereas in the nonoperative group, morbidity was 17 per cent and mortality 2 per cent. Liver resection should be considered a serious surgical option, as initial or delayed management, in patients with complex liver injury and can be accomplished with low mortality and liver-related morbidity when performed in specialized liver surgery/transplant centers.